ANALISIS STRATEGI KIAI DAN SANTRI DALAM MEWUJUDKAN KEMANDIRIAN EKONOMI PP. NURUL AMANAH DAN PP. RAUDHATUL MUTA’ALLIMIN BANGKALAN - Moh Idris; Taufiqur Rahman (MIYAH : Jurnal Studi Islam, 2021)
This research departs from the importance of identifying the economic independence in Islamic boarding schools, which functions to see phenomenologically the involvement of kiai and students in realizing the economic independence of pesantren, because so far pesantren are only seen as educational institutions and Islamic da'wah but pesantren as community empowerment institutions in Indonesia. There are still many economic fields that have not been exposed in detail and in depth. This study focuses on the objectives, knowing the strategies of kiai and santri in realizing economic independence in the Nurul Amanah Islamic Boarding School and Raudlatul Muta'allimin Islamic Boarding School and knowing the differences in strategies that exist between the two Islamic boarding schools in realizing the economic independence of Islamic boarding schools in Bangkalan. This method uses a qualitative approach where the data collection technique uses documentation, observation and thorough interviews with the kiai and several students in the two Islamic boarding schools. The results of this study conclude 1). The kiai's strategy in realizing the economic independence of pesantren is to use a capacity building strategy, strengthen institutions, transfer knowledge and strengthen networks. 2). The strategy of the santri in realizing the economic independence of the pesantren as assistant caregivers in realizing the economic independence of the pesantren. 3). The differences in the strategies carried out by the two pesantren are not much different, namely they both provide economic understanding to their students.Keyword: Strategy, Kiai, Santri, Economic Independence, Islamic Boarding School.